Childhood sexual abuse experiences of female student teachers in Zimbabwe - Gwirayi, Pesanayi; Shumba, Almon (Routledge, 2021)
The study investigated childhood sexual abuse (CSA) experiences of female student teachers in Zimbabwe. A convenience sample of 112 female respondents (mean age = 27.4 years) responded to a retrospective questionnaire which assessed childhood sexual experiences. Data were analysed descriptively. The overall prevalence rate for child sexual abuse was 43.8%. Contact CSA 42(37.5%) was slightly more common than non-contact CSA 35(31.3%). Prevalence was higher among participants who grew up in urban 42(37.5%) than in rural 7(6.3%) areas. Major perpetrators were boyfriends 70(45.5%), uncles 21(13.6%), school bursars and family friends' sons were 14(9.1%) each, respectively. Abuse occurred at the perpetrator 70(45.5%) and victim's 63(40.6%) places of residence, as well as at school 14(9.1%), and in movie houses 7(4.5%). Abuse was reported to have happened several times (45.5%), once (40.9%) and twice (13.6%). Only 7(14.3%) of the sexually victimized respondents reported the abuse.